Economic Impacts of Renewable Energy on the Economy of UAE - Jaradat, Mohammad Sulieman; AL-Tamimi, Khaled Abdalla Moh’d (International Journal of Energy Economics and Policy, 2022)
This research is concerned with the study and analysis of the economic impacts of renewable energy on the UAE’s economy. We took annual time series data for variables that include renewable energy consumption, per capita GDP, capital creation, employment, trade, inflation rate, interest rate, fixed exchange rate, foreign direct investment, and trade openness for the time period from 2010 to 2020. Initially, we applied the autoregressive distributed lag (ARDL) model to assess the long-term relationship between the variables. We encountered a multi-linearity problem where we found the correlation between the independent variables. Therefore, we adopted the alternative approach of the Ordinary Least Squares (OLS) technique to measure the relationship between renewable energy and the UAE economy. We have made an equation from OLS, in which we take renewable energy and economic growth as the independent and dependent variables, respectively. The results confirmed that there is a statistically significant relationship between renewable energy and the economy in the United Arab Emirates.